Characterization of Metals and Alloys - Pérez Campos, Ramiro; Contreras Cuevas, Antonio; Esparza Muñoz, Rodrigo A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book covers various aspects of characterization of materials in the areas of metals, alloys, steels, welding, nanomaterials, intermetallic, and surface coatings. These materials are obtained by different methods and techniques like spray, mechanical milling, sol-gel, casting, biosynthesis, and chemical reduction among others. Some of these materials are classified according to application such as materials for medical application, materials for industrial applications, materials used in the oil industry and materials used like coatings. The authors provide a comprehensive overview of structural characterization techniques including scanning electron microscopy (SEM), X-ray diffraction (XRD), transmission electron microscopy (TEM), Raman spectroscopy, image analysis, finite element method (FEM), optical microscopy (OM), energy dispersive spectroscopy (EDS), Fourier transform infrared spectroscopy (FTIR), differential thermal analysis (DTA), differential scanning calorimetry (DSC), ultraviolet-visible spectroscopy (UV-Vis), infrared photo-thermal radiometry (IPTR), electrochemical impedance spectroscopy (EIS), thermogravimetry analysis (TGA), thermo luminescence (TL), photoluminescence (PL), high resolution transmission electron microscopy (HRTEM), and radio frequency (RF). The book includes theoretical models and illustrations of characterization properties-both structural and chemical.
Part 1. Characterization of Steels Used in the Oil Industry -- Mechanical and Metallurgical Properties of Grade X70 Steel Linepipe Produced by Non-Conventional Heat Treatment -- Corrosion Inhibition of X52 Pipeline Steel in Chloride Solutions Using Non-ionic Surfactant -- Effect On The Microstructure And Mechanical Properties Of The Structural Steel Welded In Marine Environment -- Part 2. Characterization of Copper Alloys -- Mapping of Polycrystalline Flow during Hot Deformation by In-Situ Tension Test of Sheet Copper Alloy -- Determination of the Activation Energy of Copper During in-situ Tension Test by SEM -- Effect of Copper Additions on Secondary Carbide Precipitation in High-Chromium White Cast Iron -- Part. 3. Characterization of Steels Applying Heat Treatment -- Thermal Behavior of a HSLA Steel and the Impact in Phase Transformation: SAW Process Approach to Pipelines -- Effect of Hydrogen on a Microalloyed Steel Permeate -- Part 4. Characterization of Thin Layers and Coatings -- Mechanical Properties of SiO2 Coatings for Corrosion Protection of 304 Stainless Steel -- Physical Properties Characterization of CdSe1-ySy Nanolayers deposited by Chemical Bath Deposition at Low Temperature -- Part 5. Characterization of Materials Obtained by Mechanical Milling -- Magnetic Properties and Kinetic of Crystallization in Amorphous GdxSm1-xCo5 Alloys Obtained by Mechanical Milling -- Study of Mechanical Milling Mechanism in Eutectic Nanopowders: the Heterogeneities Role -- Part 6. Characterization of Materials for Medical Applications -- Biosynthesis of Silver Nanoparticles Using Extracts of Mexican Medicinal Plants -- Synthesis and Thermal Characterization of Hydroxyapatite Powders Obtained by Sol-Gel Technique -- Part 7. Characterization of Materials for Industrial Applications -- Microwave Assisted Sol-gel Synthesis and Characterization of M-TiO2 (M=Pt, Au) Photocatalysts -- Micromachined and Characterization of Cooled a-Si:B:H Microbolometer Array in Terahertz Region -- Influenceof Drilling Parameters by EDM on the HSLA Steel Microstructure -- Part 8. Characterization of Welding and Joining of Materials -- Evaluation of Distortion in Welding Unions of 304 Stainless Steel with Elliptic Trajectory Using a Welding Robot -- Weld Bead Geometry of Ni-Based Alloy Deposited by PTA Process for Pipe Conduction of Shale Gas -- Part 9. Characterization of Intermetallic Materials -- Chemical Reduction Synthesis of Iron Aluminum Powders -- Author index -- Subject index.
Keywords: Materials -- Analysis; Spectrum analysis; Metals; Characterization and Analytical Technique; Spectroscopy; Metals and Alloys